3D-FEA of Implant Thread Depth and Pitch on Interfacial Stresses. Issue 1 (March 2020) - Zhou, Yulin; Mao, Zhihong; Liu, Fan; Wang, Ruichao
Abstract: Objective: Using the numerical analysis, the interfacial stresses with various thread depths and pitches implants are evaluated in mandibular bone mass. Methods: Implant parameters considered herein include the thread depths of 0.30, 0.35, 0.40, 0.45, 0.50 and 0.55 mm and the pitches of 0.75, 0.80, 1.0 and 1.25 mm. A simplified bone-implant system is created by Geomagic studio and Solidworks. ANSYS workbench was used to analyze the effects of the stress distribution. Results: The maximum von Mises was exhibited in three position at the implant: the location between implant and abutment, the area between implant and screw and the threaded implant body (connect area between first thread and second thread or second thread and third thread). whereas uneven stress distribution were showed in both cortical bone and trabecular bone under oblique and vertical loading. Conclusions: This study found that the force (magnitude and direction) is the important factor of influence on stress, for biomechanical context, the ratio of the thread depth to the pitch at the implant below 0.55 is more appropriate for controlling the max EQV of implants.